2016
DOI: 10.1007/s13197-016-2370-1
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared and Raman spectroscopic study of the effect of the thermal treatment and extraction methods on the characteristics of ayocote bean starches

Abstract: Starches isolated from four ayocote bean varieties were modified by thermal treatment to determinate the effect of the treatment on the structural changes of ayocote bean starch. Scanning electron microscopy indicates that the starch granules have oval and round shapes, with heterogeneous sizes and fractures when the extraction method is used. The presence of new bands at 2850 and 1560 cm in the FT-IR spectra showed that the thermal treatment of ayocote beans induced an interaction between the protein or lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 27 publications
1
17
1
1
Order By: Relevance
“…Protein content in the species assayed ranged from 180.7 to 189.3 g/kg. The protein content in this study is comparable to the values of 167 to 272 g/kg, reported by Baptista et al (2017) in dry common bean varieties from Mozambique, but lower than the values of 217-238 g/kg for different Ayocote bean varieties from México (Bernardino-Nicanor et al, 2017). However, it should be noted that the protein content in edible legumes could vary significantly among cultivars of a single species (Bourges, 1987).…”
Section: Proximate Compositionsupporting
confidence: 77%
See 1 more Smart Citation
“…Protein content in the species assayed ranged from 180.7 to 189.3 g/kg. The protein content in this study is comparable to the values of 167 to 272 g/kg, reported by Baptista et al (2017) in dry common bean varieties from Mozambique, but lower than the values of 217-238 g/kg for different Ayocote bean varieties from México (Bernardino-Nicanor et al, 2017). However, it should be noted that the protein content in edible legumes could vary significantly among cultivars of a single species (Bourges, 1987).…”
Section: Proximate Compositionsupporting
confidence: 77%
“…The brown, purple, black and white varieties did not show any significant differences (P > 0.005). The lipid content was higher compared to that observed by Mosisa (2017) (9.0 g/kg) but lower than data recorded previously by Bernardino-Nicanor et al (2017) which ranged from 32.5 to 37.8 g/kg. In Mayocoba bean (P. vulgaris) lipid values of 19.8 g/kg have been reported (Osorio-Díaz, Tovar, Paredes-López, Acosta-Gallegos, & Bello-Pérez, 2005).…”
Section: Proximate Compositioncontrasting
confidence: 75%
“…This 24 hr control sample presented higher reducing sugars amounts ( p < .05) than the initial control sample, possibly by starch disruption and increased water solubility at 37°C. The starch gelatinization, produced by heating its granules in aqueous medium, generates the breakdown of its molecular order and causes irreversible changes (Bernardino‐Nicanor et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, different patterns were observed at the wavenumber region from 1,200 to 800 cm −1 , which is the fingerprint region and can be used to characterize diverse polysaccharides (Imran et al., 2016). Also, specific peaks around 770 and 864 cm −1 , related to the stretching vibration of C–O–C and C–O–H from glycosidic bonds of α‐glycosidic and β‐glycosidic linkages (Bernardino‐Nicanor et al., 2017; Capek, Drábik, & Turjan, 2010), were observed in the fermented samples (FE, FA, LP, ST, and its combinations), which could indicate a high level of starch hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…The high protein content of some pulses can be attributed to their association with the activity of the nitrogen-fixing bacteria in their roots, which converts the unusable nitrogen gas into ammonium, which the plant then incorporates into protein synthesis. In P. coccineus protein, there are approximately nine essential amino acids and are abundant in the essential amino acid lysine [6,16]. The high contents of glutamic and aspartic acids are related to their importance as starting compounds from which the backbones of the other amino acids are formed [27] (Table 5).…”
Section: Proteinsmentioning
confidence: 99%